Analisis Yuridis Penyelesaian Sengketa Kepemilikan Tanah berdasarkan Bukti Sertifikat di Pengadilan Negeri Kabupaten Probolinggo (Studi Kasus Perkara Nomor 10/Pdt.G/2023/PN Pbl) - Moh. Samsul Aji; Herdi Pratama Susantyo (AHKAM, 2025)
Land ownership disputes involving dual certificates represent a serious issue within Indonesia’s land administration system, as they directly impact legal certainty and the resolution of agrarian conflicts. This study aims to analyze the application of law in resolving land ownership disputes based on certificate evidence and to examine the judicial considerations in Decision Number 10/Pdt.G/2023/PN Pbl at the Probolinggo District Court. The research employs a normative juridical method with a case study approach. Data were obtained through literature review and analyzed using qualitative juridical analysis. The findings reveal that the court ruled in favor of the plaintiff as the rightful owner of the disputed land, based on legally valid evidence including a land ownership certificate and a legitimate deed of sale and purchase. The panel of judges considered administrative negligence and indications of bad faith in the issuance process of the second certificate. These findings affirm that land certificates serve as the primary legal evidence in guaranteeing land ownership certainty and highlight the importance of meticulous administrative practices by the National Land Agency (BPN). The study concludes that improving land administration systems and strengthening oversight of certificate issuance are strategic steps to prevent certificate overlaps. The implications of this study include theoretical contributions to the development of agrarian law scholarship and practical recommendations for BPN and the judiciary to enhance accountability and integrity in the land registration system. Future research is recommended to assess the effectiveness of implementing electronic land certificates (e-Certificates) in reducing land disputes.